Exploring the Character Education Values Embedded in East Java’s Folklore - Heru Santosa, Wijaya; Sudirman, Anselmus; Khadifa Abdul Rozzaq Wijaya, Rahmaditya (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
East Java’s folklore has inherited character education values from generation to generation because they align with relics of the Hindu-Buddhist kingdoms. This research identifies and describes character education values in East Java’s folklore. The data was gathered by critically reading the entire discourse and dialogue in the folklore texts, allowing indigenous values to be explored. Then, a content analysis was used to analyze the data concerning such values, which was classified/grouped further in line with Komensky's theories concerning the types and theme of character education values. The findings revealed that the themes of East Java’s folklore deal with not only positive character education values but also those that deviate from the models of core values, such as (1) gambling and slander in the Cindelaras story and the Banyuwangi origin story (2) crime based on envy in the Golden Conch Story, (3) coercion of will in the story of Origins of Reog Ponorogo, (4) human sacrifice offerings in the stories of Rara Anteng and Joko Seger, and (5) fear-filled environment causes chaos in Joko Dolog's tale. The importance of character education in East Java’s folklore requires teaching resources for character education integrated into various subjects, mainly studying the Indonesian language and literature. Nevertheless, before using it as a teaching tool, educators must weigh the benefits and drawbacks for their students' positive development. The importance of moral education concerning good and evil, quality, social education, and cooperation are other educational ideals that merit consideration. This evidence shows how incorporating folklore into literary works is presented through a straightforward story framework rich in moral values.